2011
DOI: 10.1088/0022-3727/44/19/194003
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of unsteady dc electric arcs and their interactions with electrodes

Abstract: This paper is devoted to the study of unsteady electric arcs and the effects of electrodes on their dynamics. One of the objectives is to simulate and understand the three-dimensional behaviour of arcs in complex geometries, which create important fluctuations of the column and reattachments on the electrodes. The usual methods to solve the problem of arc–electrodes coupling are not suitable to simulate three-dimensional unsteady arcs. We propose a numerical development to simulate both steady-state and unstea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 18 publications
0
26
1
Order By: Relevance
“…Instead the procedure of e.g. Chemartin et al [9], Larsson et al [21], and Tholin et al [12], is followed, and a thin pre-heated region of the domain is considered, representative of the initial connection resulting from voltage breakdown. This region is of sufficiently high temperature to result in ionisation and the formation of a plasma.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Instead the procedure of e.g. Chemartin et al [9], Larsson et al [21], and Tholin et al [12], is followed, and a thin pre-heated region of the domain is considered, representative of the initial connection resulting from voltage breakdown. This region is of sufficiently high temperature to result in ionisation and the formation of a plasma.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…They reported that the internal pressure between the laminate layers of the composite wind turbine blade is proportional to the arc energy that is enforced on the composite blade surface. Furthermore, the lightning plasma channel also produces a magnetic force and an acoustic shock wave, which also lead to mechanical impact damage on the composite structures (Chemartin, Lalande, Delalondre, Cheron, & Lago, 2011;Muñoz et al, 2014). An overview of the lightning strike's direct effects on polymer-matrix composite structures is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Nestor and Tsai obtained the current density profiles using experimental methods (Nestor, 1962;Tsai & Eagar, 1985). Lowke and Chemartin obtained the current density profiles using numerical methods based on magnetohydrodynamics method (MHD) (Chemartin et al, 2011;Lowke & Tanaka, 2006). The current density profiles calculated using obtained equation (4-11) and equation 4-12are compared to the experimental and numerical results.…”
Section: Lightning Current Density Spatial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, the simultaneous solution of plasma-arc and a solid has not been presented before. The interaction of the lightning arc with a surface (e.g, [16,17,18,40,41,42,43,44,45,46]) is usually done by considering prescribed plasma or prescribed material conductivity at the material interface rather than considering full solution of the two phases simultaneously.…”
mentioning
confidence: 99%